POLA INTERAKSI GURU DAN PESERTA DIDIK (Q.S Abasa ayat 1- 10) - Ita Rositawati; Abdul Ghoni (Karimiyah: Journal of Islamic Literature and Muslim Society, 2024)
The study aims to describe and analyze the ethical interactions between teachers and students according to the perspective of verses 1 through 10 of abasa letter 1 to 10 to develop the ethical concept of interacting in education and as the development of a new generation of people according to the educational purpose. Such research USES living qur 'an to incorporate research between research research (library research) and an in-depth study of tafsir thahir ibn 'the asy and field research' to find out how the qur 'an text is summarized in social life. The data-gathering technique is to find data on written data or variables, whereas the data analysis used is content analysis. In this study, a conclusion from the study, taken from the book of tafsir al-tahrir wa al-tanwir, is found an interaction ethic according to thahir ibn 'ashur: a teacher should have love, meekness, and first the needy.